130k views
3 votes
What is the solution to (x+6)(x+2)=60
x=-6
x=-4
x=4
x=12

2 Answers

3 votes

[ Answer ]


\boxed{4}

[ Explanation ]

(X + 6) * (X + 2) = 60

Plug numbers into equation:

(4 + 6) * (4 + 2) = 60

4 + 6 = 10

4 + 2 = 6

Multiply:

10 * 6 = 60


\boxed{[ \ Eclipsed \ ]}

User Irio
by
5.9k points
1 vote
soultion:
x=4

step by step
(4+6)(4+2)=60
User MDragon
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.